Apuntes para la reconstrucción de las relaciones inter- y multidisciplinares desde la lingüística en la Edad Media - González Jiménez, Juan Miguel (2025)
In this research, we analyze the contributions of medieval authors, both Christian and Islamic, with the aim of exploring the inter- and multidisciplinary relationships between linguistics and the biological and behavioral sciences in their texts. Methodologically, we employ the Theory of Textual Series and the Theory of the Canon, through which we adopt a macro-structural, dialogical and dynamic perspective, which can be found in the interaction among primary sources. The results show that the texts of Augustine of Hippo, Averroes and Thomas Aquinas tangentially develop some of the interests of biolinguistics, neurolinguistics and psycholinguistics nowadays; in particular, they focus on language versus animal communication systems, linguistic acquisition and the relationship between mind and brain/heart.